Imperial and late Latin poetry from North Africa - Kaufmann, Helen (A Companion to North Africa in Antiquity, 2022)
This chapter focuses on the poetry written in North Africa or by North African poets during the empire and late antiquity. It provides a survey of the works attested for the period in North Africa. The chapter explores characteristics of this poetry, such as language, meter, and African identities. Attributions to North Africa are usually based on one or two of the following criteria: transmission on the Codex Salmasianus, literary interaction with North African authors, (erroneous) attribution in the manuscript tradition to Cyprian, Tertullian, or Lactantius, all of them famous North Africans, and inscriptional evidence for the poet-s name in North Africa. Imperial poetry from North Africa started with a clash between a poet and an emperor. Between the Renaissance and the end of the nineteenth century the view that the Latin written by African writers was different from that in Rome found much support and the phenomenon was called Africitas..
CRIS-Team Scopus Importer:2024-12-16
Keywords: African identities; Imperial poetry; Late antiquity; Literary interaction; North African poets